Edible Film Application of Soybean Extract with the Addition of Tapioca Flour and Glycerol as A Green Grape Packer (Vitis vinifera L.) - Pratiwi, Nur Alfreda Eka; Alisaputra, Darmawan; Sedyadi, Endaruji (Proceeding International Conference on Science and Engineering, 2021)
Abstract. This research has been carried out on the manufacture and characterization of edible films made from soybean extract with tapioca flour and glycerol applied in packaging for green grapes. This study aims to determine the effect of glycerol addition on the physical properties of the resulting packaging and the effect of the repetition of grapes immersion in the packaging solution on the grapes' quality. This research's stages were the manufacture of soy milk, film formation, film characterization, water vapor transmission rate (WVTR), and application test of packaging solutions to the quality of green grapes using weight and color loss tests. A variety of glycerol (0.5; 1; 1.5; 2; 3; 5%) and the optimum yield is used to coat green grapes. The results showed that the optimum composition for making an edible film was obtained in the edible film with the addition of 2% glycerol concentration. The addition of 2% glycerol concentration can affect the physical properties of the edible film with a thickness of 0.1235mm, tensile strength of 2.4768 MPa, elongation of 66.8786%, Modulus young 0.03702 and water vapor transmission rate of 2.5306 g/m2.hours and optimum immersion variations on grape quality green found at six times immersion.